Aplicación de los modelos de gestión territorial a través de las unidades de planificación territorial, “lecciones aprendidas” (2017)
This article is the result of scientific and technological research, where concepts and guidelines are identified as well as guidelines in planning and territorial management obeying what we call the lessons learned in the context of professional and teaching practice in the planning and management approaches territorial, where new paradigm changes in territorial planning are based critically and argumentatively. Finally, for these changes, the concepts and methodologies used to carry out the new territorial planning and management approach are strategically displayed, defining the operational management tools for decision-making in the departmental and municipal context for a new model of territorial and administrative management.